Activity of IrO2 supported on tantalum-doped TiO2 electrocatalyst for solid polymer electrolyte water electrolyzer. Issue 64 (17th August 2017) - Lv, Hong; Zhang, Guanghui; Hao, Chuanpu; Mi, Cangen; Zhou, Wei; Yang, Daijun; Li, Bing; Zhang, Cunman
Abstract : TiO2 doped tantalum was successfully synthesized via an evaporation-induced self-assembly method as a support of IrO2 for a SPE water electrolyzer. The 80% IrO2 /Ti0.7 Ta0.3 O2 showed the best performance with the potential of 1.849 V at 1000 mA cm −2 . Abstract : TiO2 doped tantalum was successfully synthesized via an evaporation-induced self-assembly method (EISA) as a support of IrO2 for a solid polymer electrolyte water electrolyzer (SPEWE). The IrO2 was synthesized on the surface of Ta-doped TiO2 support by using the Adams fusion method. The samples were characterized by BET, XRD, SEM, TEM, CV, EIS and polarization curves of single cells. The doping amount of Tantalum (5, 10, 20, 30 at%) was thoroughly investigated to evaluate the effects on structure, electric conductivity and oxygen evolution reaction (OER) activity of Ta-doped titania supported IrO2 . The results indicated that a significant effect of the Ta dopant on the phase composition and conductivity. Among all the catalysts, with the optimized catalyst IrO2 loading, the terminal applied potential was 1.849 V at 1000 mA cm −2 and 80 °C in a SPE water electrolysis cell using 80IrO2 /Ti0.7 Ta0.3 O2 as anode. IrO2 loading 80% IrO2 /Ti0.7 Ta0.3 O2 showed better performance than that of the pristine IrO2 after normalizing the current density for IrO2 loading. The increased performance can be attributed to the better dispersion of the IrO2 on Ti0.7 Ta0.3 O2 resulting in smaller crystallites and large surface area. In closing, Ti0.7 Ta0.3 O2 showed outstanding promise as an electrocatalyst support in SPE water electrolysis.